2018
DOI: 10.5897/ijmms2016.1239
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasound scans for the diagnosis of pelvic inflammatory disease keeping laboratory high vaginal swab/urine microscopy culture as gold standard in Anambra State, Nigeria

Abstract: Ultrasound scanning (USS) and high vaginal swab culture and urine microscopy culture and sensitivity (m/c/s) tests are the most common investigations used for the diagnosis of pelvic inflammatory disease (PID) in our locality. The aim of this study was to determine the diagnostic accuracy of ultrasound in the diagnosis of PID keeping laboratory high vaginal swab/urine microscopy, culture as gold standard. The USS, high vaginal swab and urine m/c/s reports of patients referred with PID conditions between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This number appears low when compared with the fact that within a 9 month period in 2008 in a single hospital in Pakistan, there were 1,124 HSG cases [15]. The sharp drop in number of HSG cases in our locality may be due to the fact that ultrasound is used as the first line of investigation of infertility [8].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This number appears low when compared with the fact that within a 9 month period in 2008 in a single hospital in Pakistan, there were 1,124 HSG cases [15]. The sharp drop in number of HSG cases in our locality may be due to the fact that ultrasound is used as the first line of investigation of infertility [8].…”
Section: Discussionmentioning
confidence: 74%
“…In Radiology departments in the country, infertility is the special investigation with the highest throughput, and with ultrasound being the modality of choice for first line investigation [7]. Although ultrasound is sensitive for masses in the genital tract, it has limited sensitivity and specificity for tubal patency [8]. Hysterosalpingography (HSG) however, has high sensitivity and specificity for tubal patency [4,9], although it carries inherent radiation risks [10].…”
Section: Introductionmentioning
confidence: 99%
“…Higher prevalence of PID in women between 20-30 years of age is in accordance with the indings of Eze JC. et al (Eze et al, 2018)as this is the sexually active group. Mean age of patients was 28.23±4.97, which is in accordance with the study of Sayed A. et al (Sayed et al, 2016) (Savaris et al, 2007)reported 28.3±0.8 and 29.3±1.1yrs, in two groups.…”
Section: Baseline Characteristicsmentioning
confidence: 93%
“…Pelvic inflammatory disease (PID) is a polymicrobial disease often developed in young or child-bearing aged women . PID is characterized by upper genital tract infection endometritis, metroendometritis, parametritis, salpingo-oophoritis, and pelvic peritonitis, which may lead to developing tuboovarian abscess (Eze et al 2018). According to Xia et al (2022), the diagnosis can be directly made by ultrasound, but 100% of it can only be confirmed by hysteroscopy and histological examination of the endometrium.…”
Section: Introductionmentioning
confidence: 99%